Design and Testing of Drag and Lift Measurement Tools for Low Wind Speed Wind Tunnels - Fadilah, Muhammad Haris; Wiyono, Slamet; Erwin, Erwin (Universitas Sultan Ageng Tirtayasa, 2024)
Science and technology, including aerodynamics, are constantly advancing. Sultan Ageng Tirtayasa University has a wind tunnel in its Renewable Energy Engineering Lab but lacks equipment to measure drag and lift forces. To address this, researchers developed a measurement tool. This study involved a literature review, design, and experimental testing, including calibration to determine gauge R&R values and performance testing with the NACA S1046 airfoil. Calibration results showed standard deviations of 0.25 for drag force and 0.8 for lift force. Gauge R&R values were 0.678% for drag and 1.828% for lift, indicating acceptability. The tool performed well at 1-5 m/s but showed high lift force standard deviation at 6 m/s. The maximum test object weight is 0.7 kg.